Eco-friendly Management of Pectinophora gossypiella resistance to transgenic Bt Cotton: A Review - Hanif, Mahreen; Saeed, Shafqat; Ishtiaq, Muhammad; Ali, Mudssar; Khan, Zuluqrnain (Journal of Agriculture and Biology, 2025)
Pectinophora gossypiella (Saunders) has had a crucial ecological and economic impact on transgenic cotton production in Pakistan since 2014. For effective control of this pest, a comprehensive strategy is necessary. This article provides an overview of integrated techniques to manage P. gossypiella. This study explores the integration of various pest control strategies, including cultural, biological, and physical approaches, all intended to lower the pink bollworm infestation in an environmentally friendly manner. Cultural practices such as changing crop varieties with their sowing time, removing infested plant remnants (leftover bolls), and stacking vertically interrupt the P. gossypiella life cycle. Biological control agents like coleopteran, dipteran, etc serve to limit the P. gossypiella population naturally. The application of sex pheromones (trap) and PB ropes aids in maximizing the crop yield by reducing the pink bollworm infestation. The use of proper refuge aids increased the crop yield as well as maintain the sustainability of transgenic cotton, like in China (hybrid cultivation).  Sterile insect techniques successfully eradicate the P. gossypiella population, like in the United States. These integrated pest management (IPM) strategies have resulted in significant reductions in PBW infestation and pesticide usage, as well as improvements in yield, economic benefits, and environmental quality. For area-wide success, stakeholder cooperation and active engagement are essential, and outreach has been utilized to increase public awareness.
Keywords: Biological control; Cultural Control; Pink bollworm; PB rope; Sex Pheromone; Sterile Insect Techniques; Refuge